Magnesia blast furnace burden and low-temperature low-carbon preparation method thereof
Patent Information
- Application Number
- CN202611022463.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-10
AI Technical Summary
[0004]针对现有低温固结炉料在高炉还原和软熔滴落过程中容易出现还原膨胀加剧、软化提前、料层压差过高和透气性较差等问题,本发明的第一个目的旨在提供一种镁质高炉炉料,其具有抗压强度高,还原膨胀率低,还原度高,软熔滴性能、料层透气性较好等特点,满足高炉炼铁要求
[0032]本发明的低温低碳制备镁质高炉炉料的过程关键是在于采用了多源活化镁质添加剂,具体是采用机械活化的氧化物型镁质添加剂与特殊粒度分布的碳酸盐型镁质添加剂按照适当比例搭配使用,提高镁质添加剂在低温固结炉料中的适配性,以保证炉料在低温固结阶段具有较好的炉料成型与冷态强度,同时在后续高温还原及软熔滴落阶段能够促进含镁高熔点物相生成和渣相组成调节,从而改善炉料还原稳定性、软熔滴落性能和料层透气性。
Abstract
Description
Technical Field
[0001] This invention relates to a magnesia-based blast furnace charge, and also to a low-temperature, low-carbon preparation method for a magnesia-based blast furnace charge that regulates the high-temperature metallurgical properties of the charge through magnesium-containing additives, belonging to the field of iron and steel metallurgical technology. Background Technology
[0002] Against the backdrop of the steel industry's green and low-carbon transformation, reducing energy consumption and carbon emissions in the ironmaking process has become a crucial direction for optimizing blast furnace ironmaking processes. Sintered ore and oxide pellets are major components of blast furnace burdens, and their preparation typically requires high temperatures, accompanied by fuel consumption and carbon emissions. Taking iron concentrate agglomeration as an example, conventional oxide pellets require high-temperature processes such as drying, preheating, and roasting, resulting in high energy consumption and significant carbon emission pressure. Therefore, developing novel low-temperature, low-energy-consumption, and low-carbon-emission iron-bearing burden preparation technologies is of great significance for reducing carbon emissions in the ironmaking process and promoting the decarbonization of blast furnace smelting.
[0003] Low-temperature consolidation furnace charge mainly relies on the cementing and pressing effects of binders to form agglomerates with a certain strength from iron-containing powder at lower temperatures, eliminating the need for sintering or high-temperature roasting processes. This offers advantages such as shorter process flow, lower energy consumption, and lower carbon emissions. Existing low-temperature consolidation technologies primarily focus on raw materials such as iron ore powder, iron oxide scale, dust collector ash, and iron-containing sludge, emphasizing improving iron resource utilization, optimizing binder composition, and enhancing cold-state performance. However, compared to sintered ore and roasted pellets, low-temperature consolidation furnace charge does not undergo high-temperature mineralization reactions. Its internal structure mainly relies on particle rearrangement, mechanical interlocking, and binder phase cementation to form a consolidated structure, with a relatively insufficient high-temperature stable mineral bonding phase. During blast furnace reduction and softening dripping processes, the charge is easily affected by factors such as iron oxide reduction, volume changes, localized stress release, and the formation of low-melting-point liquid phases. This leads to problems such as intensified reduction expansion, premature softening, increased pressure differential in the material bed, and decreased permeability, limiting its stable application as blast furnace charge. Magnesium components have been used in oxide pellet systems to improve the metallurgical properties of furnace charge. Their effect mainly relies on the high-temperature mineralization reaction during roasting, which causes MgO to react with iron oxides and gangue components to form magnesium-containing high-melting-point mineral phases, thereby improving the high-temperature stability of the pellets. For example, Chinese patent application (publication number: CN107841620A) discloses a method for obtaining low-titanium magnesium pellets through pelletizing, drying, preheating, and roasting of iron concentrate powder, high-magnesium powder, and binder. These pellets exhibit superior metallurgical properties compared to high-silicate pellets. The green pellet strength meets national standards: compressive strength ≥10 N / P, drop strength ≥5 times, and bursting temperature ≥450℃; the finished pellets after roasting have a compressive strength greater than 2300 N / piece. Unlike oxidized pellets, low-temperature solidified furnace charge does not undergo high-temperature roasting and full mineralization during preparation. The magnesium components are difficult to form a stable mineral bond phase during the agglomeration stage. As a result, low-temperature solidified furnace charge is prone to problems such as aggravated reduction expansion, premature softening, excessive pressure difference in the material bed, and poor permeability during blast furnace reduction and softening dripping. Therefore, the technical approach of directly adding magnesium flux to oxidized pellets cannot be simply followed. It is necessary to carry out functional design based on the reaction characteristics of different magnesium sources to improve the reactivity and regulatory role of magnesium components in the subsequent high-temperature smelting process. Summary of the Invention
[0004] In view of the problems that existing low-temperature solidified furnace burdens are prone to intensified reduction expansion, premature softening, excessive pressure difference in the burden bed and poor permeability during blast furnace reduction and softening dripping, the first objective of this invention is to provide a magnesia blast furnace burden with high compressive strength, low reduction expansion rate, high reduction degree, good softening dripping performance and good burden bed permeability, which meets the requirements of blast furnace ironmaking.
[0005] The second objective of this invention is to provide a method for preparing magnesia-based blast furnace burden at low temperature and low carbon content. This method uses iron-containing raw materials as a matrix and introduces a multi-source activated magnesia additive formed by combining oxide-type and carbonate-type magnesia additives. The oxide-type magnesia additives undergo mechanical activation treatment to acquire high surface reactivity and high-temperature phase-forming ability. Simultaneously, the decomposition characteristics and particle size adaptation effect of the carbonate-type magnesia additives during the heating process are utilized to adjust the internal pore structure and magnesium component distribution of the burden. Therefore, the burden's forming and cold strength are ensured during the low-temperature consolidation stage, and the formation of high-melting-point magnesium-containing phases and slag phase composition are promoted during the subsequent high-temperature reduction and softening / drip stages, thereby improving the burden's reduction stability, softening / drip performance, and bed permeability.
[0006] To achieve the above-mentioned technical objectives, the present invention provides a method for preparing low-temperature, low-carbon magnesia blast furnace burden, comprising the following steps: S1: Mix iron-containing raw materials, multi-source activated magnesium additives, binders and water to obtain a mixture;
[0007] The multi-source activated magnesium additives include carbonate-type magnesium additives and oxide-type magnesium additives; the oxide-type magnesium additives undergo mechanical activation treatment, and their particle size distribution meets the following requirements: particles with a diameter less than 74 μm account for no less than 80.0 wt.%, particles with a diameter less than 45 μm account for no less than 40.0 wt.%, and the surface area is no less than 100 m² / g; the carbonate-type magnesium additives meet the following requirements: particles with a diameter less than 74 μm account for no less than 60.0 wt.%, and particles with a diameter less than 45 μm account for no less than 20.0 wt.%.
[0008] The carbonate-type magnesium additive and the oxide-type magnesium additive are measured by the mass of MgO they provide, and their compositions are: 25.0 wt.% to 60.0 wt.% and 40.0 wt.% to 75.0 wt.%.
[0009] S2: The mixture is subjected to high-pressure roller molding to obtain magnesia raw agglomerates; S3: The magnesia raw agglomerates are consolidated to obtain magnesia blast furnace charge.
[0010] The key to preparing high-performance magnesia blast furnace burdens in this invention lies in the use of multi-source activated magnesia additives. Specifically, based on the different characteristics of various magnesia sources in the low-temperature solidification burden system, multiple magnesia sources with different activities, functions, and particle sizes are combined. Among them, oxide-type magnesia additives, with MgO as the main magnesium component, can directly participate in the interfacial and solid-phase reactions between iron oxides, SiO2, Al2O3, and the binder phase at high temperatures. However, its reactivity is greatly affected by particle size, surface structure, and crystal stability. In contrast, oxide-type magnesia additives activated by mechanical ball milling have a higher specific surface area, further refined particle size, and form new surfaces, microcracks, and surface defect structures on the particle surface, thereby improving their surface reactivity and high-temperature phase formation ability. Carbonate-type magnesium additives maintain a suitable particle size distribution, ensuring good dispersion in the mixture. During the calcination of the agglomerates, they undergo thermal decomposition to form active MgO components. Simultaneously, they regulate the internal pore structure and reducing gas diffusion conditions of the furnace charge. Thus, by combining the two, the high-temperature phase-forming effect of oxide-type magnesium additives and the decomposition and pore-regulating effect of carbonate-type magnesium additives can be combined, thereby achieving synergistic regulation of the magnesium-containing components on the structural stability, phase transformation behavior, and softening and dripping performance of the furnace charge.
[0011] More specifically, in low-temperature solidified furnace charge systems, if only binder bonding and external pressing are relied upon to improve cold strength, the charge may still experience structural deterioration during high-temperature reduction and softening dripping due to insufficient high-temperature stable bonding phases. This invention introduces multi-source activated magnesium additives, making the activated oxide-type magnesium additives more readily react or dissolve with components such as SiO2, Al2O3, FeO, and Fe2O3 at high temperatures. This promotes the formation of magnesium-containing high-melting-point phases such as Mg2SiO4, MgSiO3, MgAl2O4, and MgFe2O4, as well as magnesium-containing solid solutions, thereby enhancing the high-temperature structural stability of the furnace charge. Simultaneously, the active MgO component formed by the decomposition of carbonate-type magnesium additives during heating can further participate in phase transformation and alleviate local expansion stress during reduction through pore structure adjustment. After entering the softening dripping stage, the magnesium-containing components can also participate in the adjustment of the composite slag phase composition. On the one hand, the formation of magnesium-containing high-melting-point phases is beneficial to improving the high-temperature stability of the furnace charge, delaying the softening process of the furnace charge, and providing more favorable conditions for the full indirect reduction reaction. On the other hand, after the magnesium-containing components enter the slag phase, they can regulate the liquid phase generation temperature, slag phase flow characteristics and slag-iron separation behavior, thereby reducing the resistance of the softening and dripping process and the pressure difference of the material layer, improving the permeability of the furnace charge and the adaptability of blast furnace smelting.
[0012] The ratio of oxide-type magnesium additives to carbonate-type magnesium additives in this invention is optimized. Oxide-type magnesium additives have excellent high-temperature phase-forming effects, while carbonate-type magnesium additives have decomposition and pore-regulating effects. When the two are combined in an appropriate ratio, the problems of concentrated reaction stages or insufficient high-temperature control ability of a single magnesium source can be avoided.
[0013] As a preferred embodiment, the carbonate-type magnesium additive includes at least one of magnesite powder, magnesium carbonate (specifically, for example, light magnesium carbonate), and basic magnesium carbonate. A preferred carbonate-type magnesium additive is a magnesium raw material with MgCO3 and / or basic magnesium carbonate as the main magnesium-containing component. MgCO3 or basic magnesium carbonate readily decomposes at high temperatures to produce active magnesium oxide, while simultaneously generating gas to regulate the microporous structure.
[0014] As a preferred embodiment, the oxide-type magnesium additive includes magnesium oxide powder. More preferably, it is at least one of lightly calcined magnesium oxide powder and activated magnesium oxide powder. The preferred oxide-type magnesium additive has a high MgO content and, after mechanical activation treatment, has a higher specific surface area, as well as higher surface reactivity and high-temperature phase-forming ability.
[0015] As a preferred embodiment, the oxide-type magnesium additive, measured on a dry basis, has an MgO content of 70.0 wt.% to 99.0 wt.% and an oxidation loss on ignition of 0 wt.% to 15.0 wt.%.
[0016] As a preferred embodiment, the carbonate-type magnesium additive, measured on a dry basis, has an MgO content of 35.0 wt.% to 55.0 wt.% and an oxidation loss on ignition of 35.0 wt.% to 60.0 wt.%.
[0017] The magnesium oxide content and loss on ignition range of the oxide-type and carbonate-type magnesium additives of this invention are beneficial to ensuring that the two types of magnesium additives respectively play a role in stabilizing magnesium supply and regulating decomposition. The oxide-type magnesium additive has a high MgO content, which, after mechanical activation, can participate in high-temperature interfacial reactions and the formation of magnesium-containing high-melting-point phases as a stable MgO source. The carbonate-type magnesium additive has suitable MgO equivalent and loss on ignition characteristics, which can undergo decomposition reactions during heating to form active MgO components and regulate the internal pore structure of the furnace charge. By limiting the composition of the oxide-type and carbonate-type magnesium additives, the regulatory effect of multi-source activated magnesium additives on the high-temperature metallurgical properties of the furnace charge can be improved.
[0018] As a preferred embodiment, the amount of the multi-source activated magnesia additive added is 1.0 wt.% to 8.0 wt.% based on the total dry weight of the iron-containing raw material, the multi-source activated magnesia additive, and the binder. If the amount of multi-source activated magnesia additive added is too low, the magnesium-containing components will not adequately regulate the behavior of the high-temperature phases and slag phases. If the amount of multi-source activated magnesia additive added is too high, it will, on the one hand, alter the particle size distribution and binder phase distribution of the mixture, increasing the difficulty of forming and reducing the compaction density and cold strength of the agglomerates; on the other hand, it will increase the proportion of gangue components in the furnace charge, reduce the iron content, and increase the slag volume and smelting load in the subsequent blast furnace smelting process. Therefore, controlling the multi-source activated magnesia additive within the above-mentioned range is beneficial for balancing the furnace charge forming performance, cold strength, iron content, and high-temperature metallurgical performance.
[0019] As a preferred embodiment, the iron-containing raw material includes at least one of iron concentrate, iron ore powder, iron oxide scale, and iron-containing dust. The iron-containing raw material, measured on a dry basis, has a total iron content (TFe) of not less than 50 wt.%. The aforementioned iron-containing raw materials have a wide range of sources and can be selected based on mine raw material conditions and the availability of secondary iron resources in the steel enterprise, which is beneficial for improving raw material adaptability and resource utilization efficiency. Controlling the TFe content of the iron-containing raw material within a range of not less than 50 wt.% ensures that the resulting furnace charge has a necessary iron grade foundation, avoiding an increase in gangue load, a decrease in finished product grade, and an increased blast furnace smelting load due to an excessively high proportion of low-grade raw materials.
[0020] As a preferred embodiment, the adhesive comprises organic binder components and inorganic binder components.
[0021] As a preferred embodiment, the composition of the organic binder component and the inorganic binder component is 5.0 wt.% to 25.0 wt.% : 75.0 wt.% to 95.0 wt.%.
[0022] As a preferred embodiment, the organic binder component includes at least one of polyacrylamide, sodium lignosulfonate, molasses, sodium carboxymethyl cellulose, and epoxy resin.
[0023] As a preferred embodiment, the inorganic binder component includes at least one of bentonite, sodium silicate, potassium silicate, silica sol, silicate cement, and geopolymer cementitious materials.
[0024] As a preferred embodiment, the binder is measured by the total dry weight of the iron-containing raw material, the multi-source activated magnesium additive, and the binder, and its addition amount is 2.0 wt.% to 7.0 wt.%.
[0025] The binder of the present invention, through the compounding of organic and inorganic binder components, can take into account the plasticity, particle adhesion and structural strength after low-temperature consolidation during the molding process of the mixture. Furthermore, by controlling the amount of binder added and the ratio of organic to inorganic components within a suitable range, it is beneficial to improve the molding quality, cold strength and low-temperature consolidation stability of the new magnesia blast furnace charge.
[0026] As a preferred embodiment, the linear pressure used in the high-pressure roller forming process is 0.6 t / mm to 1.0 t / mm. An appropriate amount of water is added during the high-pressure roller forming process; for example, the amount of water added makes the forming moisture content of the mixture 4.0 wt.% to 10.0 wt.%. The above-mentioned forming pressure and moisture range are beneficial for the formation of a stable particle contact structure and binder phase distribution in the mixture, thereby improving the forming quality of the magnesium agglomerates.
[0027] As a preferred embodiment, the consolidation conditions are: consolidation at a low temperature of 80℃ to 200℃ for 3 to 120 minutes. During the consolidation process, microwave heating, hot air heating, or infrared heating can be used. These low-temperature consolidation conditions can promote the curing of the binder and the removal of moisture from the lumps, obtaining a new type of magnesia-based blast furnace charge that meets the requirements for transportation, storage, and furnace loading without sintering or high-temperature roasting.
[0028] The mechanical activation treatment of this invention employs one or more of the following methods in combination: high-energy planetary ball milling, high-pressure roller milling, and rod milling. The activation degree is such that the particle size distribution of the oxide-type magnesium additive meets the following requirements: the proportion of particles with a diameter less than 74 μm is not less than 80.0 wt.%, the proportion of particles with a diameter less than 45 μm is not less than 40.0 wt.%, and the specific surface area measured by the BET method is not less than 100 m². 2 / g. The above particle size and specific surface area range are beneficial to improving the solid-phase reaction efficiency between oxide-type magnesium additives and iron-containing particles, gangue components and binder phases, and enhancing their ability to participate in phase transformation at high temperatures.
[0029] The present invention also provides a magnesia-based blast furnace charge, which is obtained by the aforementioned preparation method.
[0030] As a preferred embodiment, the linear pressure during the high-pressure roller forming process is 0.6 t / mm to 1.0 t / mm. The amount of water added is such that the forming moisture content of the mixture is 4.0 wt.% to 10.0 wt.%. The above forming pressure and moisture range are beneficial for the mixture to form a stable particle contact structure and binder phase distribution, thereby improving the forming quality of the magnesium agglomerates.
[0031] Compared with the prior art, the technical solution of the present invention brings the following beneficial effects:
[0032] The key to the low-temperature, low-carbon preparation process of magnesia blast furnace charge of this invention lies in the use of multi-source activated magnesia additives. Specifically, mechanically activated oxide-type magnesia additives and carbonate-type magnesia additives with special particle size distribution are used in appropriate proportions to improve the compatibility of magnesia additives in low-temperature consolidation charge, so as to ensure that the charge has good charge forming and cold strength in the low-temperature consolidation stage. At the same time, in the subsequent high-temperature reduction and softening dripping stages, it can promote the formation of high-melting-point magnesium-containing phases and adjust the slag phase composition, thereby improving the reduction stability, softening dripping performance and permeability of the charge layer.
[0033] On the one hand, since low-temperature consolidation furnace charge mainly relies on particle rearrangement, mechanical interlocking, and binder phase cementation to form a consolidated structure, the particle size distribution, dispersion state, and surface reactivity of magnesium additives directly affect the molding performance and cold strength of the mixture. When the magnesium additive particles are too coarse or unevenly distributed, local enrichment areas are easily formed in the mixture, weakening the effective bonding between iron particles, magnesium additives, and the binder phase, thus forming low-strength areas inside the agglomerates, leading to molding difficulties, decreased compressive strength, and insufficient structural stability at high temperatures. This invention mechanically activates oxide-type magnesium additives to refine their particle size and form new surfaces, microcracks, and defect structures on the particle surface, improving their surface reactivity and high-temperature phase formation ability. At the same time, the particle size distribution of carbonate-type magnesium additives is optimized to maintain good dispersion uniformity in the mixture, avoiding the impact of local enrichment on agglomerate molding and consolidation strength. Therefore, the present invention can take into account the molding adaptability, dispersion uniformity and subsequent high-temperature reaction capability of magnesium additives, which is beneficial to improving the cold performance and high-temperature metallurgical performance of new magnesium blast furnace charge.
[0034] Secondly, this invention achieves synergistic regulation of magnesium-containing components during high-temperature reduction and softening dripping processes by compounding oxide-type magnesium additives and carbonate-type magnesium additives in an appropriate ratio. For low-temperature solidified furnace burdens without the introduction of magnesium functional components, since their preparation process does not undergo high-temperature mineralization reactions during sintering or roasting, the high-temperature stable mineral bonding phase is relatively insufficient. During blast furnace reduction and softening dripping processes, they are easily affected by factors such as iron oxide reduction, volume changes, local stress release, and the formation of low-melting-point liquid phases, leading to problems such as intensified reduction expansion, premature softening, increased pressure differential of the burden layer, and deterioration of permeability. This invention, through mechanical activation, enables oxide-type magnesium additives to participate in high-temperature interfacial and solid-phase reactions in the form of highly active MgO, and react or dissolve with components such as SiO2, Al2O3, FeO, and Fe2O3, promoting the formation of magnesium-containing high-melting-point phases such as Mg2SiO4, MgAl2O4, and MgFe2O4. This enhances the high-temperature structural stability of the burden, delays the softening process, and provides conditions for the full occurrence of indirect reduction reactions. Carbonate-type magnesium additives undergo thermal decomposition during heating, generating active MgO components. These components, released into the gas phase, regulate the internal pore structure of the furnace charge and the diffusion conditions of reducing gases, thus helping to alleviate local expansion stress during reduction. After entering the dripping stage, the magnesium-containing components can also participate in the regulation of the composite slag phase composition, influencing the liquid phase formation temperature, slag flow characteristics, and slag-iron separation behavior. This reduces the resistance during the softening and dripping process and the pressure difference in the material bed, improving the permeability of the furnace charge and its adaptability to blast furnace smelting.
[0035] The magnesia blast furnace charge preparation process of this invention adopts a route combining high-pressure roller forming and low-temperature consolidation, realizing low-temperature, low-carbon agglomeration of iron-containing raw materials while taking into account both cold strength and high-temperature metallurgical properties of the charge. Since the preparation processes of sintered ore and oxide pellets typically rely on high-temperature heat treatment and external fuel heating, energy consumption and carbon emissions are relatively high. Although ordinary low-temperature consolidation charges can reduce the agglomeration temperature, they often suffer from insufficient high-temperature mineral bonding phases and poor high-temperature metallurgical properties. This invention mixes iron-containing raw materials, multi-source activated magnesia additives, composite binders, and water, and directly produces a novel magnesia blast furnace charge through high-pressure roller forming and low-temperature consolidation. This eliminates the need for sintering or high-temperature roasting processes, reducing the dependence of the agglomeration process on high-temperature heat treatment and external fuel heating, and features a short process, low energy consumption, and low carbon emissions. Meanwhile, the composite binder helps improve the forming stability and cold strength of the furnace charge during the low-temperature consolidation stage, meeting the requirements for transportation, storage, and use in the furnace; the multi-source activated magnesium additive plays a role in phase regulation and slag phase adjustment during the subsequent high-temperature reduction and softening dripping process. In summary, this invention improves the blast furnace smelting adaptability of low-temperature consolidation furnace charge while reducing energy consumption and carbon emissions in the ironmaking process, providing a new technical approach for optimizing blast furnace charge structure and reducing carbonization in ironmaking processes. Detailed Implementation
[0036] To facilitate understanding of the present invention, the following description will be more comprehensive and detailed in conjunction with preferred embodiments, but the scope of protection of the present invention is not limited to the following specific embodiments.
[0037] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of the invention.
[0038] Unless otherwise specified, the various reagents and raw materials used in this invention are commercially available products or products that can be prepared by known methods.
[0039] The relevant standards for performance testing of cold-pressed blocks in the following embodiments are as follows: compressive strength test standard is GB / T 14201-2018, ISO 4700:2015; low-temperature reduction pulverization index test standard is GB / T 31923-2015; reduction performance test standard is GB / T 13241-2017; iron ore-high temperature load reduction softening dripping performance test method is GB / T 34211-2017.
[0040] Example 1
[0041] (1) Iron concentrate is selected as the iron-containing raw material, wherein the iron concentrate has a TFe content of 64.92 wt.% and an FeO content of 1.04 wt.%; magnesium oxide powder is selected as the oxide-type magnesium additive, wherein the MgO content is 95.50 wt.% and the loss on ignition under an oxidizing atmosphere is 0.72 wt.%; magnesite powder is selected as the carbonate-type magnesium additive, wherein the MgO content is 42.30 wt.% and the loss on ignition under an oxidizing atmosphere is 47.60 wt.%.
[0042] (2) The magnesium oxide powder was mechanically activated using high-energy planetary ball milling for 15 minutes at a ball-to-powder mass ratio of 5:1 and a rotation speed of 350 r / min. After mechanical activation, the proportion of particles smaller than 74 μm in the magnesium oxide powder was 97.50 wt.%, and the proportion of particles smaller than 45 μm was 60.30 wt.%. The specific surface area measured by the BET method was 198 m². 2 / g; The proportion of particles with a diameter less than 74μm in magnesite powder is 72.40wt.%, and the proportion of particles with a diameter less than 45μm is 31.60wt.%.
[0043] (3) The mechanically activated magnesium oxide powder and magnesite powder are compounded according to the MgO equivalent, wherein the MgO provided by the oxide type magnesium additive accounts for 60.0 wt.% of the total MgO equivalent, and the MgO provided by the carbonate type magnesium additive accounts for 40.0 wt.% of the total MgO equivalent, thus obtaining a multi-source activated magnesium additive.
[0044] (4) Based on the total dry weight of the iron-containing raw material, multi-source activated magnesium additive, and binder, the amount of multi-source activated magnesium additive added is 4.0 wt.%, the amount of binder added is 4.0 wt.%, and the balance is iron concentrate. The binder is composed of organic binder and inorganic binder in a ratio of 10 wt.% : 90 wt.%. The organic binder is composed of 45 wt.% sodium carboxymethyl starch, 45 wt.% sodium carboxymethyl cellulose, and 10 wt.% epoxy resin. The inorganic binder is composed of 15 wt.% sodium silicate, 40 wt.% sodium silicate, 30 wt.% silica sol, and 15 wt.% bentonite.
[0045] (5) Mix the iron concentrate, multi-source activated magnesium additive, composite binder and water evenly, and control the moisture content of the mixture to 7.0 wt.% to obtain the mixture.
[0046] (6) The mixture is formed by high pressure roller molding with a linear pressure of 0.80t / mm to obtain magnesium raw agglomerates.
[0047] (7) The magnesia raw lumps are placed in a hot air drying device for low-temperature consolidation. The consolidation temperature is 105℃ and the consolidation time is 40min. After cooling, a new type of magnesia blast furnace charge is obtained.
[0048] The test results show that the compressive strength of the new magnesia blast furnace charge obtained in this embodiment is 2680 N / piece, the reduction expansion rate is 18.20%, the reduction degree is 81.75%, the maximum pressure difference during the softening and dripping process is 12.20 kPa, and the S characteristic value is 1080 kPa·℃.
[0049] Example 2
[0050] This embodiment is basically the same as embodiment 1, except that:
[0051] The iron-containing raw material is a mixture of iron ore powder and iron oxide scale, wherein the iron ore powder accounts for 85.0 wt.% of the iron-containing raw material and the iron oxide scale accounts for 15.0 wt.%, and the TFe content of the mixed iron-containing raw material is 61.80 wt.%.
[0052] The oxide-type magnesium additive is active magnesium oxide powder with an MgO content of 97.20 wt.% and a loss on ignition of 1.01 wt.%; the carbonate-type magnesium additive is light magnesium carbonate with an MgO content of 43.80 wt.% and a loss on ignition of 52.30 wt.%.
[0053] The activated magnesium oxide powder was mechanically activated using a high-pressure roller mill. After treatment, the proportion of particles smaller than 74 μm in the activated magnesium oxide powder was 88.70 wt.%, the proportion of particles smaller than 45 μm was 52.40 wt.%, and the BET specific surface area was 174 m². 2 / g; The proportion of particles with a diameter less than 74μm in light magnesium carbonate is 80.20wt.%, and the proportion of particles with a diameter less than 45μm is 42.50wt.%.
[0054] Based on MgO equivalent, oxide-type magnesium additives provide 50.0 wt.% of the total MgO equivalent, and carbonate-type magnesium additives provide 50.0 wt.% of the total MgO equivalent. The amount of multi-source activated magnesium additives added is 5.0 wt.%, the amount of binder added is 4.5 wt.%, and the moisture content of the mixture during molding is 7.5 wt.%. The high-pressure roller forming line pressure is 0.90 t / mm, the low-temperature consolidation method is microwave heating, the consolidation temperature is 120℃, and the consolidation time is 5 min.
[0055] The test results show that the compressive strength of the new magnesia blast furnace charge obtained in this embodiment is 2845 N / piece, the reduction expansion rate is 17.97%, the reduction degree is 82.64%, the maximum pressure difference during the softening and dripping process is 11.11 kPa, and the S characteristic value is 823 kPa·℃.
[0056] Example 3
[0057] This embodiment is basically the same as embodiment 1, except that:
[0058] The iron-containing raw material is a mixture of iron concentrate and iron-containing dust, wherein the iron concentrate accounts for 90.0 wt.% of the iron-containing raw material and the iron-containing dust accounts for 10.0 wt.%, and the TFe content of the mixed iron-containing raw material is 58.60 wt.%.
[0059] The oxide-type magnesium additive is light-burned magnesia powder with an MgO content of 97.40 wt.% and a loss on ignition of 1.44 wt.%; the carbonate-type magnesium additive is magnesium carbonate. The light-burned magnesia powder was mechanically activated using a rod mill. After treatment, the proportion of particles smaller than 74 μm was 84.60 wt.%, and the proportion of particles smaller than 45 μm was 46.20 wt.%. The specific surface area, measured by the BET method, was 241 m². 2 / g; The proportion of particles with a diameter less than 74μm in magnesium carbonate is 68.50wt.%, and the proportion of particles with a diameter less than 45μm is 28.70wt.%.
[0060] Based on MgO equivalent, oxide-type magnesium additives provide 70.0 wt.% of the total MgO equivalent, while carbonate-type magnesium additives provide 30.0 wt.% of the total MgO equivalent. The amount of multi-source activated magnesium additives added is 3.0 wt.%, the amount of binder added is 5.0 wt.%, and the moisture content of the mixture during molding is 8.0 wt.%. The high-pressure roller forming line pressure is 0.75 t / mm, the low-temperature consolidation method is infrared heating, the consolidation temperature is 140℃, and the consolidation time is 25 min.
[0061] The test results show that the compressive strength of the new magnesia blast furnace charge obtained in this embodiment is 3079 N / piece, the reduction expansion rate is 19.97%, the reduction degree is 84.64%, the maximum pressure difference during the softening and dripping process is 9.71 kPa, and the S characteristic value is 755 kPa·℃.
[0062] Comparative Example 1
[0063] This comparative example is basically the same as Example 1, except that: no multi-source activated magnesium additive is added, and the remaining iron-containing raw materials, binder addition amount, molding moisture, high pressure roller forming line pressure and low temperature consolidation conditions are the same as in Example 1.
[0064] The test results showed that the compressive strength of the low-temperature consolidation furnace charge obtained in this comparative example was 2610 N / piece, the reduction expansion rate was 26.33%, the reduction degree was 80.33%, the maximum pressure difference during the softening and dripping process was 17.60 kPa, and the S characteristic value was 2120 kPa·℃.
[0065] Compared with Example 1, without the addition of multi-source activated magnesium additives, the reduction expansion rate of the furnace charge during high-temperature reduction was significantly increased, and the maximum pressure difference and S characteristic value during the softening and dripping process were also significantly increased. This indicates that magnesium-containing functional components have a positive effect on improving the high-temperature structural stability and softening and dripping performance of the low-temperature solidified furnace charge.
[0066] Comparative Example 2
[0067] This comparative example is basically the same as Example 2, except that: the oxide-type magnesium additive is not mechanically activated, but is directly compounded with the carbonate-type magnesium additive in the same MgO equivalent ratio and then added. The other raw material ratios, molding moisture, molding pressure and low-temperature solidification conditions are the same as in Example 2.
[0068] In the unactivated oxide-type magnesium additive, particles with a diameter less than 74 μm accounted for 63.20 wt.%, particles with a diameter less than 45 μm accounted for 24.50 wt.%, and the BET specific surface area was 134 m². 2 / g.
[0069] The test results showed that the compressive strength of the magnesium low-temperature consolidation furnace charge obtained in this comparative example was 2480 N / piece, the reduction expansion rate was 18.70%, the reduction degree was 81.74%, the maximum pressure difference during the softening and dripping process was 13.90 kPa, and the S characteristic value was 1230 kPa·℃.
[0070] Compared to Example 2, the oxide-type magnesium additive, without mechanical activation treatment, has a coarser particle size, lower specific surface area, and insufficient surface reactivity and contact reaction efficiency, which is detrimental to the formation of high-melting-point magnesium-containing phases at high temperatures. Therefore, it negatively impacts the compressive strength of the furnace charge, and its improvement effect on reduction expansion and softening dripping behavior is weaker than in Example 2. This indicates that mechanical activation treatment of the oxide-type magnesium additive is an important measure to improve the high-temperature metallurgical properties of the furnace charge.
[0071] Comparative Example 3
[0072] This comparative example is basically the same as Example 3, except that: no carbonate-type magnesium additive is added, only an oxide-type magnesium additive that has been mechanically activated is added, and the MgO equivalent provided by it is consistent with the total MgO equivalent provided by the multi-source activated magnesium additive in Example 3. The other iron-containing raw materials, the amount of composite binder added, the molding moisture, the pressure of the high-pressure roller forming line and the low-temperature consolidation conditions are the same as those in Example 3.
[0073] The test results showed that the compressive strength of the magnesium low-temperature consolidation furnace charge obtained in this comparative example was 2930 N / piece, the reduction expansion rate was 24.60%, the reduction degree was 82.51%, the maximum pressure difference during the softening and dripping process was 11.35 kPa, and the S characteristic value was 1490 kPa·℃.
[0074] Compared to Example 3, while adding only oxide-type magnesium additives can provide stable MgO composition and promote the formation of high-melting-point magnesium-containing phases to some extent, it lacks the thermal decomposition, active MgO replenishment, and pore structure regulation effects of carbonate-type magnesium additives during heating. Therefore, its improvement effect on reducing gas diffusion conditions, local expansion stress release, and softening dripping behavior is limited. These results indicate that the combination of oxide-type and carbonate-type magnesium additives can exert a synergistic regulatory effect, which is superior to the single magnesium source addition scheme.
Claims
1. A method for preparing low-temperature, low-carbon magnesia blast furnace burden, characterized in that: Includes the following steps: S1: Mix iron-containing raw materials, multi-source activated magnesium additives, binders and water to obtain a mixture; The multi-source activated magnesium additives include carbonate-type magnesium additives and oxide-type magnesium additives; The oxide-type magnesium additive undergoes mechanical activation treatment, and its particle size distribution meets the following requirements: particles with a diameter less than 74 μm account for no less than 80.0 wt.%, particles with a diameter less than 45 μm account for no less than 40.0 wt.%, and the surface area is no less than 100 m². 2 / g; The particle size distribution of the carbonate-type magnesium additive meets the following requirements: particles with a diameter less than 74 μm account for no less than 60.0 wt.%, and particles with a diameter less than 45 μm account for no less than 20.0 wt.%. The carbonate-type magnesium additive and the oxide-type magnesium additive are measured by the mass of MgO they provide, and their compositions are: 25.0 wt.%–60.0 wt.% : 40.0 wt.%–75.0 wt.%; The carbonate-type magnesium additive includes at least one of magnesite powder, magnesium carbonate, and basic magnesium carbonate. The oxide-type magnesium additive includes at least one of light-burned magnesium oxide powder and active magnesium oxide powder; The oxide-type magnesium additive, measured on a dry basis, has an MgO content of 70.0 wt.% to 99.0 wt.% and an oxidation loss on ignition of 0 wt.% to 15.0 wt.%. The carbonate-type magnesium additive, measured on a dry basis, has an MgO content of 35.0 wt.% to 55.0 wt.% and an oxidation loss on ignition of 35.0 wt.% to 60.0 wt.%. The multi-source activated magnesium additive, measured by the total dry weight of the iron-containing raw material, the multi-source activated magnesium additive, and the binder, is added in an amount of 1.0 wt.% to 8.0 wt.%. S2: The mixture is subjected to high-pressure roller molding to obtain magnesium raw lumps; S3: Consolidate the magnesia raw lumps to obtain magnesia blast furnace charge.
2. The method for preparing low-temperature, low-carbon magnesia blast furnace burden according to claim 1, characterized in that: The iron-containing raw materials include at least one of iron concentrate, iron ore powder, iron oxide scale, and iron-containing dust and sludge.
3. The method for preparing low-temperature, low-carbon magnesia blast furnace burden according to claim 1, characterized in that: The adhesive includes organic binder components and inorganic binder components; The composition of the organic binder and the inorganic binder is 5.0 wt.% to 25.0 wt.% and 75.0 wt.% to 95.0 wt.%, respectively.
4. The method for preparing low-temperature, low-carbon magnesia blast furnace burden according to claim 3, characterized in that: The organic binder component includes at least one of polyacrylamide, sodium lignosulfonate, molasses, sodium carboxymethyl cellulose, and epoxy resin; The inorganic binder component includes at least one of bentonite, sodium silicate, potassium silicate, silica sol, silicate cement, and geopolymer cementitious materials. The binder is measured by the total dry weight of the iron-containing raw materials, multi-source activated magnesium additives and the binder, and its addition amount is 2.0 wt.% to 7.0 wt.%.
5. The method for preparing low-temperature, low-carbon magnesia blast furnace burden according to claim 1, characterized in that: The linear pressure used in the high-pressure roller forming process is 0.6t / mm to 1.0t / mm.
6. The method for preparing low-temperature, low-carbon magnesia blast furnace burden according to claim 1, characterized in that: The consolidation conditions are: consolidation at a low temperature of 80℃ to 200℃ for 3 min to 120 min.
7. A magnesia-based blast furnace charge, characterized in that: It is obtained by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparing method for low-titanium magnesium iron ore pellets
CN107841620A
Ultra-micro magnesium carbonate pellet additive, preparation method thereof, and application thereof
CN102373332A
Method for preparing high-quality magnesian pellets by strengthening magnesium-containing magnetite concentrate
CN116479235A
Method for low-carbon preparation of high-reactivity blast furnace burden from magnetite concentrate and blast furnace burden
CN120700272A